The quality of water: perception and senses of fluid movement. (2nd September 2022) - Heath, Sean
ABSTRACT: This paper examines tactile sensory dimensions of immersion in water and is based on ethnographic fieldwork amongst competitive youth swimmers in the South East of England. It argues that youth swimmers' perceptions of the qualities of water, in the pools where they train and compete, are sensuous productions of embodied knowledges and enskilled movements developed and refined through their swimming practice. Thus, it adds to the growing anthropological literature on the senses and physical movement practices by suggesting that the cultural sensory order developed in competitive swimming privileges touch sense modalities. Swimmers must develop a "feel for the water, " the skills and sensory perceptions to assess and assist their interaction with the medium of water. Learning to feel is an ongoing dialectic process of making sensory knowledge developed through an accumulation of regular immersion and occasional absence. This paper asserts that the making of "feel for the water" is an essential element in youth swimmers' self formation, incorporating their growing and physically changing bodies as experienced through their immersion in a "mirror" environment in constant motion.